Does atrial fibrillation deteriorate the prognosis in patients with septic or cardiogenic shock? - Schupp, Tobias; Forner, Jan; Rusnak, Jonas; Weidner, Kathrin; Egner-Walter, Sascha; Ruka, Marinela; Dudda, Jonas; Jawhar, Schanas; Brück, Lea Marie; Dulatahu, Floriana; Bertsch, Thomas; Müller, Julian; et al. (The American journal of cardiology, 2023)
Atrial fibrillation (AF) is associated with increased risk of mortality in various clinical conditions. However, the prognostic role of preexisting and new-onset AF in critically ill patients, such as patients with septic or cardiogenic shock remains unclear. This study investigates the prognostic impact of preexisting and new-onset AF on 30-day all-cause mortality in patients with septic or cardiogenic shock. Consecutive patients with sepsis, or septic or cardiogenic shock were enrolled in 2 prospective, monocentric registries from 2019 to 2021. Statistical analyses included Kaplan-Meier, multivariable logistic, and Cox proportional regression analyses. In total, 644 patients were included (cardiogenic shock: n = 273; sepsis/septic shock: n = 361). The prevalence of AF was 41% (29% with preexisting AF, 12% with new-onset AF). Within the entire study cohort, neither preexisting AF (log-rank p = 0.542; hazard ratio [HR] 1.075, 95% confidence interval [CI] 0.848 to 1.363, p = 0.551) nor new-onset AF (log-rank p = 0.782, HR = 0.957, 95% CI 0.683 to 1.340, p = 0.797) were associated with 30-day all-cause mortality compared with non-AF. In patients with AF, ventricular rates >120 beats/min compared with ≤120 beats/min were shown to increase the risk of reaching the primary end point in AF patients with cardiogenic shock (log-rank p = 0.006, HR 1.886, 95% CI 1.164 to 3.057, p = 0.010). Furthermore, logistic regression analyses suggested increased age was the only predictor of new-onset AF (odds ratio 1.042, 95% CI 1.018 to 1.066, p = 0.001). In conclusion, neither the presence of preexisting AF nor the occurrence of new-onset AF was associated with the risk of 30-day all-cause mortality in consecutive patients admitted with cardiogenic shock.